1992
DOI: 10.1136/bmj.305.6865.1326
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of asthma in adults in Busselton, Western Australia.

Abstract: Objective-To estimate whether the prevalence of asthma in adults increased over a nine year interval. Design-Serial cross sectional studies of the population with a protocol that included both subjective and objective measurements.Setting-Busselton, Western Australia. Subjects-A random sample of 553 subjects aged 18-55 years in 1981, and of 1028 subjects aged 18-55 years in 1990. Main outcome measures-Respiratory symptoms measured by self administered questionnaire, bronchial responsiveness measured by bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
2
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(78 citation statements)
references
References 21 publications
4
71
2
1
Order By: Relevance
“…The rates of symptoms in adults were similar to those found in a study of adults in Busselton, Western Australia using an identical protocol [10]. Because few of the adults studied were older than 50 yrs, misclassification due to the presence of chronic airflow limitation was unlikely.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The rates of symptoms in adults were similar to those found in a study of adults in Busselton, Western Australia using an identical protocol [10]. Because few of the adults studied were older than 50 yrs, misclassification due to the presence of chronic airflow limitation was unlikely.…”
Section: Discussionsupporting
confidence: 65%
“…The prevalence of recent wheeze (in the last 12 months) in Australian children doubled from approximately 12% in 1982 to 24% in 1992, and the prevalence of airway hyperresponsiveness (AHR) also doubled in this period but only in atopic children [9]. However, a similar comparison of adults in 1981 and 1990 showed that the prevalence of recent wheeze increased only in subjects less than 30 yrs of age and that the prevalence of AHR had not increased at all, even in atopic subjects [10].…”
mentioning
confidence: 94%
“…In this study conducted among 955 school children from two schools in Thrissur the prevalence of asthma was found to be 10.4%.This is lower than other studies 9 and higher than most of Indian studies like study by Amir et al 10 , Prasad et al 11 etc. Prevalence of adult asthma in the study done in Kerala was 5.4%.Asthma prevalence among school children in the other studies were 8.4-10.3%.…”
Section: Discussioncontrasting
confidence: 48%
“…It is the most common chronic disease of childhood and an important cause of absence from school and reduced participation in sports and other activities [2]. Several studies, for example in UK and Australia, have revealed a substantial increase in the prevalence of the disease among children over the last 3 decades [3][4][5][6][7][8]. While some of this maybe due to changes in diagnostic practice, there is general agreement that the increase in the prevalence of symptoms is a true phenomenon [9][10][11].…”
Section: Introductionmentioning
confidence: 99%